Isolation of an intermediate which precedes dnaG RNA polymerase participation in enzymatic replication of bacteriophage phi X174 DNA. - Weiner, J H (1976)
Conversion of phi X174 single-stranded DNA to the duplex replicative form (RF) in vitro requires at least 10 purified proteins. Three stages - strand initiation, elongation, and termination - comprise this conversion. We now identify a separate stage in strand initiation which precedes dnaG RNA polymerase participation. Incubation of five proteins - protein i, protein n, DNA unwinding protein, dnaB protein, and dnaC protein - with ATP and phi X174 DNA forms an intermediate which enables subsequent stages measured by DNA synthesis to proceed 20 times faster. The intermediate can be isolated in quantitative yield by gel filtration or by ultracentrifugation. Protein i and protein n are required in less than stoichiometric amounts and appear to be absent from the isolated intermediate. Whereas formation of the intermediate is sensitive to antibody to protein i and to N-ethylmaleimide (an inhibitor of protein n and dnaC protein), the intermediate itself is resistant to these reagents. DNA unwinding protein complexes the DNA in a ratio of 60 molecules per circle. Synthesis of the intermediate appears to require stoichiometric quantities of dnaB protein and dnaC PROTEin but their presence in the intermediate has not been established as yet.